2020
DOI: 10.4081/idr.2020.8728
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tuberculosis Program Management in Primary Health Care

Abstract: Background: This study discusses the analysis of Tuberculosis (TB) program management at the Perak Timur Primary Health Care (PHC) and the Sawahan PHC in Surabaya. Early detection and adequate treatment can prevent transmission and improve control programs. Objective: This study aims to analyze management of the tuberculosis program at PHCs in Surabaya. Methods: The research method used is qualitative research. Data collection was done by interviewing tuberculosis officers about TB program and carrying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…23,28 Several countries including South Africa, Egypt and Indonesia have long adopted this plan where TB services are essentially provided at the PHC level. 24,25,29 We found that only half of the PHCs could produce the national treatment guidelines when prompted to do so. According to the WHO, this document provides guidance for effective diagnosis and treatment and, adherence to TB treatment guidelines is crucial to achieving cure while at the same time preventing the emergence of drug resistance.…”
Section: Discussionmentioning
confidence: 95%
“…23,28 Several countries including South Africa, Egypt and Indonesia have long adopted this plan where TB services are essentially provided at the PHC level. 24,25,29 We found that only half of the PHCs could produce the national treatment guidelines when prompted to do so. According to the WHO, this document provides guidance for effective diagnosis and treatment and, adherence to TB treatment guidelines is crucial to achieving cure while at the same time preventing the emergence of drug resistance.…”
Section: Discussionmentioning
confidence: 95%
“…Pulmonary TB is the most common infectious disease and one of the leading global causes of mortality from infectious diseases (3)(4)(5)(6). In addition, pulmonary TB is a threat because the cure rate is still low (2,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%